Macropinocytosis as a potential mechanism driving neurotropism of Cryptococcus neoformans - Lanser, Dylan M.; Bennett, Amelia B.; Vu, Kiem; Gelli, Angie (Frontiers in Cellular and Infection Microbiology, 2023)
Cryptococcus neoformans can invade the central nervous system by crossing the blood-brain barrier via a transcellular mechanism that relies on multiple host factors. In this narrative, we review the evidence that a direct interplay between C. neoformans and brain endothelial cells forms the basis for invasion and transmigration across the brain endothelium. Adherence and internalization of C. neoformans is dependent on transmembrane proteins, including a hyaluronic acid receptor and an ephrin receptor tyrosine kinase. We consider the role of EphA2 in facilitating the invasion of the central nervous system by C. neoformans and highlight experimental evidence supporting macropinocytosis as a potential mechanism of internalization and transcytosis. How macropinocytosis might be conclusively demonstrated in the context of C. neoformans is also discussed.